Аналіз морфемного складу неологізмів засобами сучасних інформаційних технологій (на основі англійської мови) - Карамишева, І.; Карамишева, Р. (Лексикографічний бюлетень, 2006)
The presented article focuses on the morphemic analysis of English neologisms, namely those created by means of blend compounding. It has been found out that the base of such neologisms possesses vague semantic motivation, which hinders its correct interpretation. The IT means are not ready to facilitate their proper morphological analysis. The solution to this problem may lie in the creation of the new word stems’ database.